2019
DOI: 10.3390/w11030583
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination of Irrigation Water, Soil, and Vegetables and the Difference between Dry and Wet Seasons Near a Multi-Industry Zone in Bangladesh

Abstract: Heavy metal (Cr, Cu, Zn, As, Cd, and Pb) contamination in irrigation water, soil, and vegetables was investigated in farmland adjacent to a multi-industry zone in Bangladesh in dry and wet seasons. In the zone, many factories release wastewater into nearby irrigation canals, and vegetables cultivated with this water could be a major food chain route for human exposure. In the irrigation water and vegetables, heavy metal concentrations exceeded permissible levels in the two seasons, but this was not the case in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…BCF >1 indicate that the heavy metals are easily taken up by plants from the soil through the plants organs and these organs accumulate these heavy metals and BCF <1 indicate that spinach absorbed these heavy metals but did not store them ( Chopra and Pathak, 2012 ). It has been reported that BCF ratio >0.20 indicates high contamination of vegetables by human activities hence high risk to health ( Ahmed et al., 2019 ). The BCF ratios of the heavy metals during the first month were >0.2 but the spinach was not ready for harvest during the time hence low public health risk.…”
Section: Resultsmentioning
confidence: 99%
“…BCF >1 indicate that the heavy metals are easily taken up by plants from the soil through the plants organs and these organs accumulate these heavy metals and BCF <1 indicate that spinach absorbed these heavy metals but did not store them ( Chopra and Pathak, 2012 ). It has been reported that BCF ratio >0.20 indicates high contamination of vegetables by human activities hence high risk to health ( Ahmed et al., 2019 ). The BCF ratios of the heavy metals during the first month were >0.2 but the spinach was not ready for harvest during the time hence low public health risk.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, contamination of the food chain, leading to potential health risks, is one of the major environmental pathways of human exposure to potentially harmful elements (PHEs) [3]. Thus, more and more studies have been conducted on the contamination of edible plants with PHEs and the related health-risk implications [3,4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Human activities and development depend essentially on water [ 1 , 2 ]. Water pollution and associated problems are increased with the rapid progress of urbanization, industrialization, and the direct release of various contaminants such as heavy metals into clean water sources [ 3 , 4 ]. The hard degradation of heavy metals, their persistence, toxicity, and mobility in water sources have made these ions the most dangerous of all contaminants.…”
Section: Introductionmentioning
confidence: 99%